「客家源流與形成研究」專題導論 - 羅烈師; Lieh-shih Lo (國立陽明交通大學客家文化學院, 2021)
本文的主要目的，在於對「客家源流與形成研究」這一專題所收錄的三篇論文進行簡介。一方面，林正慧和羅烈師的論文處理的是「客家形成」問題，特別是粵東嘉應州和臺灣新竹縣兩地之「客人論述」的形成。另一方面，許維德的論文則是以「客家源流」既有文獻的回顧為主要關懷，透過「理念型」和「連續體」這兩個概念的運用，作者提出了一個相對另類的客家源流回顧架構。

This introduction reviews the three articles presented in this special issue. On the one hand, the focus of Cheng-hui Lin's and Lieh-shih Lo's articles is the “Hakka formation” issue, especially the emergence of “Hagngin discourse” in both Jiaying Zhou of Eastern Guangdong and Hsin Chu Country of Taiwan. On the other hand, Wei-der Shu's article attempts to provide a literature review of “Hakka origin” research, especially through the lens borrowed from the concept of “ideal types” and “continuum.”
Introduction: Studies of Hakka Origin and Formation
Keywords: 客家源流; 客家形成; 客人論述; Hakka Origin; Hakka Formation; Hagngin Discourse